Q&A - Ask Doubts and Get Answers

Clear All
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is  true                 For  n = k  we have    ,        Let's assume that this is true Now, For  n = k + 1  we have                                                                                                                                                                                                             ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is divisible by 27, hence true                 For  n = k  we have    ,        Let's assume that this is divisible by  27  = 27m Now, For  n = k + 1  we have                                                                                                                                                                   ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is divisible by 8, hence true                 For  n = k  we have    ,        Let's assume that this is divisible by  8   = 8m Now, For  n = k + 1  we have                                                                                                                                                                     ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is divisible by    , hence true                 For  n = k  we have    ,        Let's assume that this is divisible by     Now, For  n = k + 1  we have                                                                                                                                                                         ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is divisible by 11, hence true For  n = k  we have    ,        Let's assume that this is divisible by 11 = 11m Now, For  n = k + 1  we have                                                                                                                                                                                     ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is multiple of 3, hence true For  n = k  we have    ,        Let's assume that this is multiple of 3 = 3m Now, For  n = k + 1  we have                                                                                                                                                                                           ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                   ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                  ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                   ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                   ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                   ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                               ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                   ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                 ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                   ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                   ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                   ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                    ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                    ...
Let the given statement be p(n) i.e. For n = 1  we have    ,   which is true For  n = k  we have    ,        Let's assume that this statement is true Now, For  n = k + 1  we have                                                                                                                                                                                                                  ...
Exams
Articles
Questions